Analisis Kinerja Keuangan Pemerintah Daerah Kabupaten Maluku Tengah - Matulatuwa, Antagracea; Pelamonia, Julie Th.; Asrida, Wa (Journal of Applied Accounting, 2024)
This research aims to measure the financial performance of the Regional Government of Central Maluku Regency based on the Value For Money concept, namely from an economic, efficiency, and effectiveness perspective. The type of research used in this research is case study research with a quantitative descriptive approach. The data used is the Regional Revenue and Expenditure Budget Realization Report of the Regional Government of Central Maluku Regency for 2016 to 2020. Data was obtained from the Regional Financial and Asset Management Agency of Central Maluku Regency. The data analysis technique in this research uses the concept of value for money with economic ratios, efficiency, and effectiveness. The results of this research show that the financial performance of the Regional Government of Central Maluku Regency based on the Value for Money ratio is quite good. The economic ratio in 2016 was 93.09% which is included in the economic category. From 2017 to 2019 the economic ratio decreased to 89.29%; 89.90% and 86.62% are in the quite economical category. In 2020, the economic ratio increased by 91.06% and was within economic criteria. Meanwhile, for the performance efficiency ratio, in 2016 the performance efficiency ratio was 93.29% and was in the less efficient category. During 2017 to 2020 this ratio fluctuated, namely 85.48%; 82.29%; 80.70%, and 86.51%, and are included in the criteria of being quite efficient. The financial performance effectiveness ratio from 2016 to 2020 is included in the effective criteria where the ratio is 95.84%; 92.84%; 95.47%; 95.20% and 96.62%. Keywords: financial performance, value for money